Effect of Smoking on Concentration of Carboxyhemoglobin for Persons with β-Thalassemia Minor - LAURA PALARIE, DANIELA; PREDA, MIRCEA; PALARIE, ION (Asian Journal of Chemistry, 2010)
Percentages of carboxyhemoglobin (HbCO) from human venous blood have been determined for four categories of subjects: healthy persons and individuals with β-thalassemia minor, each of these two classes have also been divided into smokers and non-smokers. Identification of β-thalassemic individuals has been realized by performing hemoglobin electrophoresis on agarose gel. Multicomponent analysis based on absorption spectra of hemoglobin has been used in order to obtain HbCO concentrations. Increased values of HbCO have been determined in the blood of smokers, about 6 % for healthy persons while 10 % for those with β-thalassemia minor.